'One Hand Washes the Other' in EU's Eastern Neighbourhood: What Policy Response?. Issue 5 (17th November 2020) - Buscaneanu, Sergiu; Stefes, Christoph H.
Abstract: The institutions of patronage, clientelism and nepotism are resilient and obstruct political liberalisation and democratic consolidation. This paper draws on historical (neo)institutionalism, democratisation research and studies in economic history to understand the reproduction mechanisms of informal institutions in EU's Eastern neighbourhood, and to propose a policy response, which could have the potential to disrupt these mechanisms. Outsourcing national judiciary systems from EU's Eastern neighbourhood to external rule of law missions might offer one solution as long as they satisfy at least two conditions: (1) they need to have a targeted executive mandate; and (2) they must be deployed with the support of an authoritative international actor, such as the EU or UN, under conditions of concerted international efforts and significant financial assistance. Local actors might oppose this infringement of national sovereignty. External rule of law missions should therefore be proposed during a democratic transition when reformers rely on external support.